2021
DOI: 10.1111/ppe.12762
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity at delivery and postpartum readmission in the United States

Abstract: Background Little is known about the extent to which severe maternal morbidity (SMM) at delivery impacts early and late postpartum readmission. Objectives We examined readmission rates for women with and without SMM (and their 18 subtypes) at delivery and characterised the most common medical reasons for readmissions. Methods We conducted a retrospective cohort study utilising the 2016‐2017 Nationwide Readmissions Database among women giving births in the United States. Deliveries were classified according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
2
15
1
Order By: Relevance
“…( The non-Hispanic Black terminology is used to be consistent with Center for Disease Control and vital statistics reporting .). Non-Hispanic Black ( referred to hereafter as Black ) women also have higher rates of emergency department visits and hospital readmissions in the first 6 weeks after birth, also indicators of maternal morbidity, than Whites (Johnson et al, 2019; Matas et al, 2021; Wang et al, 2020). A recent systematic review reported that Black women had an adjusted risk ratio (RR) for SMM of 1.2–5 compared with Whites (Wang et al, 2020).…”
mentioning
confidence: 99%
“…( The non-Hispanic Black terminology is used to be consistent with Center for Disease Control and vital statistics reporting .). Non-Hispanic Black ( referred to hereafter as Black ) women also have higher rates of emergency department visits and hospital readmissions in the first 6 weeks after birth, also indicators of maternal morbidity, than Whites (Johnson et al, 2019; Matas et al, 2021; Wang et al, 2020). A recent systematic review reported that Black women had an adjusted risk ratio (RR) for SMM of 1.2–5 compared with Whites (Wang et al, 2020).…”
mentioning
confidence: 99%
“…For each maternal death, it is estimated that there are 20 or more cases of severe maternal morbidity [17]. The incidence of severe maternal morbidity is approximately 1.6% in North America, 1.2% in Australia, and 0.7% in the Netherlands [16,[18][19][20]. Variation in incidence is partly due to differences in the definition and measurement of severe maternal morbidity.…”
Section: Prevalencementioning
confidence: 99%
“…Hypertensive disorders in pregnancy (HDP) are one of the most common causes for obstetric-related readmissions. 1 Previous studies have published postpartum readmission rates due to HDP ranging from 0.4% to 9.3%. 2 , 3 , 4 , 5 , 6 Severe maternal morbidities related to postpartum hypertension and preeclampsia include stroke, eclampsia, and death.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 , 6 Severe maternal morbidities related to postpartum hypertension and preeclampsia include stroke, eclampsia, and death. 1 , 7 Between 2014-2017, HDP comprised 6.6% of pregnancy-related deaths. 8 These serious risks are why prompt and thorough evaluations are warranted for patients who exhibit any signs or symptoms of HDP in pregnancy and postpartum.…”
Section: Introductionmentioning
confidence: 99%